Modeling of an Extraction Steam Turbine and Speed Control System Design - Abdullah, H. M.; Mustafa, G.; Chaudri, K. S.; Abid, M. (The Nucleus, 2021)
Steam-driven power plants essentially convert mechanical energy into electrical energy by using steam turbines. It is imperative to control the speed of the turbines as the frequency of the power system depends on it. This paper presents a model of a steam turbine containing three steam extractions from the intermediate-pressure section and four extractions from the low- pressure section. The underlying methodology for modeling is the continuity equation of a steam vessel. As the input variables, the model uses the valve opening degree of different valves, namely high-pressure valve, reheater valve, intermediate-pressure steam extraction valve and low-pressure steam extraction valve. The model behavior is observed against each input variable. It is then subsequently used to design the speed control system of the steam turbine using the proportional and proportional-integral controllers. The response of the speed control system is analyzed for both types of controllers and different valve openings. Simulation results demonstrate that the proposed model is suitable to study the dynamic behavior of an extraction steam turbine and for the feedback control system design.